The Effect of Propping on the Performance of the Financial Industry in Indonesia - Putri, Verlina Anggita Kartika; Supatmi, Supatmi (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This study aims to determine the effect of related party transactions propping on the financial industry's financial performance and performance market performance. This research sample is 66 financial industry companies listed on the Stock Exchange Indonesia (IDX) during 2017-2019 with 198 observations as panel data. Based on the panel data regression test, this research found propping proxied by related party transactions account payables, related party transactions with other payables and related party transactions liabilities other than account payables do not positively affect the company's financial performance (ROA). Propping is proxied by related party transactions, account payables, and liabilities other than account payables do not positively affect the market performance of industrial companies' finance. Meanwhile, propping proxied by transactions of other debt-related parties positively affects financial industry companies' market performance (Tobin's Q). The findings align with transaction cost theory and the efficient transaction hypothesis that related party transactions are efficient transactions to boost company performance.